Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

If the sum of the 6th and 7th terms of an arithmetic progression is 60 and the 3rd term is -5, find the common difference.

Sagot :

Sure, let's solve this problem step by step.

Given:
1. The sum of the 6th and 7th terms of an arithmetic progression (AP) is 60.
2. The 3rd term of the AP is -5.

We can use the following notations:
- Let [tex]\( a \)[/tex] be the first term of the arithmetic progression.
- Let [tex]\( d \)[/tex] be the common difference of the progression.

The general formula for the [tex]\( n \)[/tex]-th term of an AP is given by:
[tex]\[ a_n = a + (n-1)d \][/tex]

### Step 1: Determine the expressions for the relevant terms.
- The 3rd term of the AP [tex]\( a_3 \)[/tex] can be written as:
[tex]\[ a_3 = a + 2d \][/tex]
- The 6th term of the AP [tex]\( a_6 \)[/tex] can be written as:
[tex]\[ a_6 = a + 5d \][/tex]
- The 7th term of the AP [tex]\( a_7 \)[/tex] can be written as:
[tex]\[ a_7 = a + 6d \][/tex]

### Step 2: Use the given information.
- From the given information, we know:
[tex]\[ a + 5d + a + 6d = 60 \][/tex]
This simplifies to:
[tex]\[ 2a + 11d = 60 \][/tex]

- We are also given that the 3rd term is -5:
[tex]\[ a + 2d = -5 \][/tex]

### Step 3: Solve the system of equations.
We have two equations now:
1. [tex]\( 2a + 11d = 60 \)[/tex]
2. [tex]\( a + 2d = -5 \)[/tex]

Let's solve these equations simultaneously.

Equation 1:
[tex]\[ 2a + 11d = 60 \][/tex]

Equation 2:
[tex]\[ a + 2d = -5 \][/tex]

We can multiply Equation 2 by 2 to facilitate elimination:
[tex]\[ 2(a + 2d) = 2(-5) \][/tex]
[tex]\[ 2a + 4d = -10 \][/tex]

Now we have:
1. [tex]\( 2a + 11d = 60 \)[/tex]
2. [tex]\( 2a + 4d = -10 \)[/tex]

Subtract the second equation from the first equation to eliminate [tex]\( a \)[/tex]:
[tex]\[ (2a + 11d) - (2a + 4d) = 60 - (-10) \][/tex]
[tex]\[ 2a + 11d - 2a - 4d = 60 + 10 \][/tex]
[tex]\[ 7d = 70 \][/tex]

### Step 4: Solve for [tex]\( d \)[/tex].
[tex]\[ d = \frac{70}{7} \][/tex]
[tex]\[ d = 10 \][/tex]

### Conclusion:
The common difference [tex]\( d \)[/tex] of the arithmetic progression is [tex]\( 10 \)[/tex].